Calculation of DC arc plasma torch voltage-current characteristics based on Steenbeck model - Gnedenko, V.G.; Ivanov, A.A.; Pereslavtsev, A.V.; Tresviatsky, S.S. (Вопросы атомной науки и техники, 2006)
Modern technology of treatment of waste and equilibrium plasma chemistry is based on plasma technology of gas heating using the direct current arc plasma torches. The work is devoted to the problem of the determination of plasma torches parameters and power sources parameters (working voltage and current of plasma torch) at the predesigning stage. The sequence of calculation of voltage-current characteristics of DC arc plasma torch is proposed. It is shown that the simple Steenbeck model of arc discharge in cylindrical channel makes it possible to carry out this calculation. The results of the calculation are confirmed by the experiments. Современная технология обработки отходов и равновесной плазмохимии основана на плазменной технологии нагрева газа, используя плазменные горелки дуги постоянного тока. Работа посвящена проблеме определения параметров плазменных горелок и параметров источников питания (рабочее напряжение и ток плазменной горелки) на стадии проектирования. Предложена последовательность расчета вольт-амперных характеристик плазменной горелки дуги постоянного тока. Показано, что простая модель Штейнбека дугового разряда в цилиндрическом канале делает возможным провести этот расчет. Результаты расчета подтверждены экспериментами. Сучасна технологія обробки відходів та рівноважної плазмохімії основана на плазмовій технології нагріву газу, використовуючи плазмові горілки дуги сталого струму. Робота присвячена проблемі визначення параметрів плазмових горілок та параметрів джерел живлення (робочої напруги та струму плазмової горілки) на стадії проектування. Запропонована послідовність розрахунку вольт-амперних характеристик плазмової горілки дуги сталого струму. Показано, що проста модель Штейнбека дугового розряду в циліндричному каналі робить можливим провести цей розрахунок. Результати розрахунку підтверджені експериментами.